2012
DOI: 10.1088/0022-3727/45/13/135102
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet detection using TiO2 nanowire array with Ag Schottky contact

Abstract: The glancing angle deposition technique has been employed to synthesize TiO2 nanowire (NW) arrays which have been characterized by x-ray diffraction, field emission-scanning electron microscopy and high resolution transmission electron microscopy. Optical absorption measurements show the absorption edge at 3.42 eV and 3.48 eV for TiO2 thin film (TF) and NW, respectively. The blue shift in absorption band is attributed to quantum confinement in NW structures. Photoluminescence measurement revealed oxygen-defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Annealed sample shows a strong and sharp PL peaks at 400 nm, 452 nm in the PL Spectrum as shown in Fig.4. It is found that PL intensity increased gradually after annealing at 800 o C. The emission peaks at 400 nm (3.1 eV) was due to main band transition and Er related trapped states was attributed for emission [35,36,38] at 452 nm (~2.74 eV) [37][38][39][40][41] which has a good agreement with the value calculated from optical absorption measurement. …”
Section: Optical Absorption Analysissupporting
confidence: 68%
See 1 more Smart Citation
“…Annealed sample shows a strong and sharp PL peaks at 400 nm, 452 nm in the PL Spectrum as shown in Fig.4. It is found that PL intensity increased gradually after annealing at 800 o C. The emission peaks at 400 nm (3.1 eV) was due to main band transition and Er related trapped states was attributed for emission [35,36,38] at 452 nm (~2.74 eV) [37][38][39][40][41] which has a good agreement with the value calculated from optical absorption measurement. …”
Section: Optical Absorption Analysissupporting
confidence: 68%
“…The optical band gap value close to ~ 3.3 eV (375 nm) and ~3.1 eV (400) was responsible for the TiO 2 main band transition for the as deposited and the 800 0 C annealed sample respectively. The band gap value ~ 2.76 eV was attributed to the Er related trapped states [35][36][37][38][39][40][41]. So, these results reveal that the doping of erbium oxide (Er 2 O 3 ) created a small red shift of 0.2 eV on the band gap value of the host material due to the formation of T-O-Er bond when annealed at 800 o C. Figure 4 shows the PL spectrum of Er 2 O 3 NP decorated TiO 2 NW at an excitation wavelength of 250 nm using F-7000 FL spectrophotometer.…”
Section: Optical Absorption Analysismentioning
confidence: 99%
“…The pine tree leaf shaped NWs were formed due to the deposition of perpendicular components of incoming atomic flux. 19 The EDAX analysis (Fig. 1(d)) shows the presence of Titanium (Ti) and oxygen (O 2 on the samples.…”
Section: Formation Of Tio 2 Nanowiresmentioning
confidence: 99%
“…Enhanced scattering of incident photons increased the optical absorption, which leads to improve electron-hole pair generation process. 12,13 Higher number of charge carriers can be generated in NRs-based device compared to TF counterpart whose optical absorption is relatively low. Additionally, metal-semiconductor NR array geometry can introduce a radial junction at the metal semiconductor interface whereas a planar junction is formed at the TF device.…”
Section: Figures 1(a) and 1(b) Show The Sem Images Of Cross Sectionalmentioning
confidence: 99%
“…Additionally, larger aspect ratio of 1D nanostructures also contribute toward efficient trapping of the incident radiation via diffuse light scattering and enhanced optical absorption. 12,13 Previously, TiO 2 1D nanostructures fabricated by glancing-angle deposition (GLAD) 12,13 and hydrothermal growth technique 14,15 have been reported for the realization of highly sensitive Schottky type photodetectors. The observed enhanced photoresponsivity was attributed to the modification of oxygen species adsorbed at surface of TiO 2 nanorods (NRs) under illumination and trapped incident photons.…”
Section: Introductionmentioning
confidence: 99%